Defuzzification in the process of managerial estimating the value of agricultural lands - Ostapchuk, Tetiana; Orlova, Kateryna; Biriuchenko, Svitlana; Dankevych, Andrii; Marchuk, Galyna (My University, 2021)
The main purpose of the research is to substantiate the methodological approach of defuzzification and to define its peculiarities in the process of estimating the value of agricultural lands

Основною метою дослідження є обґрунтування методологічного підходу дефазифікації та визначити її особливості в процесі оцінки вартості с.-г. землі
Keywords: agricultural lands; defuzzification; управління діяльністю сільськогосподарських підприємств; сільськогосподарські угіддя; вартість землі; дефазифікація; land value; кафедра економіки і права